Cultural Intelligence and Work Engagement amongst Employees in MTN Lagos State, Nigeria: A Cross-Sectional Survey - Omorodion Omoregbe; Walter Omatsola Ajuniye-Boyo; Joseph Azage (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2025)
This study examined the effect of cultural intelligence on the work engagement of employees in MTN operating in Lagos State. It specifically assessed the influence of cognitive, metacognitive, motivational, and behavioural cultural intelligence on employee work engagement. A correlational cross-sectional survey research design was adopted. The population comprised 372 employees across MTN service centres in Lagos State, and a census approach was used. Data were collected through a structured questionnaire and analysed using descriptive statistics, including means and standard deviations, as well as multiple regression analysis to test the hypotheses. The findings revealed that metacognitive cultural intelligence had the strongest positive influence on work engagement (β = .771, p < 0.05), followed by cognitive cultural intelligence (β = .514, p < 0.05) and behavioural cultural intelligence (β= .313, p < 0.05). However, motivational cultural intelligence showed no significant effect (β= -.132, p > 0.05). The study concludes that developing multiple dimensions of cultural intelligence simultaneously enhances employee work engagement more effectively than focusing on individual dimensions. It recommended that organizations implement comprehensive cultural intelligence training programs to improve engagement.